Energy-efficient thermoelectric unit for microclimate control on cattlebreeding premises. (November 2020) - Tikhomirov, Dmitry A.; Trunov, Stanislav S.; Kuzmichev, Aleksey V.; Rastimeshin, Sergey.A.; Shepovalova, Olga.V.
Abstract: The microclimate control for animals is the mandatory condition of ecological compatibility of agricultural industry and production of high-quality products, protection of both the animals and products and, hence, people who consume such products from the harmful influence of technical progress. The goal of research was to develop an air dehumidifier based on Peltier elements for ensuring optimal microclimate parameters on cattle breeding premises. Advantages notwithstanding, there are no Peltier element-based dehumidifiers for such conditions. The functional–technological scheme and method for calculating the parameters of the thermoelectric installation for dehumidifying, heating and disinfecting the air in livestock buildings are presented. The parameters and modes of its operation are substantiated. The results of physical simulations of air dehumidification and heating processes are reported. The design structure of the thermoelectric unit's operating sample and the results of its testing are presented. As a result of the research, it was found out that the thermal energy extracted by the hot circuit and used to heat the dehumidified air exceeds the electric energy consumed from the power grid by 20% to 30%. The use of the proposed units instead of traditional ones will enable the consumer to reduce his energy costs by a maximum of 30%. The dehumidifiers are designed for application on agricultural premises of small volume characterized by required air capacity of about 500 m 3 /h, such as maternity rooms, prophylactorium calf houses, veterinary sanitary centers, etc. The research performed allows to create a typical size spectrum for dehumidifiers within the specified range of capacity. For their application on cattle breeding premises where a high air capacity is required, additional research is needed. The price of developed thermoelectric dehumidifier of power up to 5 kW and air capacity of up to 500 m 3 /h (600 − 700 $) is comparable with that of conventional air dehumidifiers. The estimated annual economic effect of this equipment introduction into a commercial dairy farm for 800 livestock units will be circa $9000.